OPTIMIZATION OF CONDITIONS FOR FERMENTATIVE PRODUCTION AND EXTRACTION β - GALACTOSIDASE Kluyveromyces marxianus - Gamarra-Ballena, G. (2000)
Five strains of Kluyveromyces marxianus a one of Gandida pseudotropicalis were cultured in medium M· 1 for productión of β-galactosidase (E.C: 3:2:1:23). The strain Kluyveromyces marxianus NRRL- Y - 1109 was selecteed for the best production (11.6 U/ml). The maximum yield of enzyme (1330 U ONPG/g of biomass) was obtained on 5% of lactose supplemented with 0.5% yeast extract , 0.75% (NH4)2SO4 y 0.45% K2HPO4 (W/V). The best extraction of the enzyme from viable cells was performed by toluene 2% (v/v), at pH 7.0 ± 0.1, 30ºC during 15 hours of treatment, in 0.1 M potassium phosphate buffer, supplemented with 1 mM magnesium and 0.1 mM manganese sulfate. The enzyme was partially purified with acetone. lt obtained a specific activity of de 73 U LACTOSA/mg of protein and a yield of 93.3%. Optimun pH and temperature for enzyme activity were pH 6.6 and 40°C. The Km for lactose was 15 mM and Vm of 7.3X10^(-5) M/min.